Linguacultural types of personalities: leader, authority - Damina Shaibakova, Gulnara Abdiyeva, Gibadat Orynkhanova,; Marina Mukhanova, Yessenkul Uisinbayeva, (Opción, 2020)
This article presents the results of one stage of modeling linguocultural type’s leader and authority, which differ in social- status specificity in the modern linguoculture. Their conceptual, figurative and evaluation characteristics based on dictionaries and NCRL (National Corpus of the Russian Language) and associative experiment were described. As a result, linguocultural concept differs from other units by its mental nature. The mentality is perceived as a controlled collection of images and perceptions. We can conclude that the leader is an influential, serious man who knows what he wants from life.